Texts awarded in the second edition of the Prof. Boris Parashkevov Student Competition for Translation from German (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2023)
Translated texts awarded in the second edition of the Prof. Boris Parashkevov Student Competition for Translation from German (2023)